From Education to Employment: Developing Soft Skills and Employability.Case of Cadi Ayyad University Career Center - Aissaoui, Tayeb; Ouskou, Rachid; Lakhlili, Ibtissame (International Journal of Scientific Research and Management (IJSRM), 2024)
This work aims to study the role played by university career centers in strengthening the employability of young students, and more specifically the case of the career center of the Cadi Ayyad University of Marrakech. The relevance of this subject stems from the importance of improving employability, but also from the role of public institutions in supporting it in alignment with the concerns of companies. The resolution of this work involves a documentary study of the data developed by the Career Center, and more, a qualitative study of the focus group of the center's advisors.